(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
The fundamental basis of the radical reforms being implemented in the new Uzbekistan is the implementation of state policy aimed at creating conditions for human and spiritual living, and the historical significance of the strategic programs adopted by the head of state and their results are analyzed in this article.